BUSINESS EDUCATION STUDENTS’ RATING OF FACTORS INFLUENCING CAREER CHOICE IN UNIVERSITIES IN EDO AND DELTA STATES (NAU Journal of Technology and Vocational Education, 2024)
This study investigated business education students rating of factor influencing career choice inuniversities in Edo and Delta States. The theory of this study was hinged on Krumboltz' theory ofsocial learning and career decision making. The descriptive survey research design wasemployed and the population for the study consist of 802 Business education undergraduatestudents from University of Benin and Delta State University. The sample size comprised 100Business education undergraduate students selected through a proportionate samplingtechnique. The instrument used for data collection was structured questionnaire. The reliabilityof the instrument was 0.71. The data collected were analyzed using mean (࢞̅(, standard deviationand two sample independent t-test. The findings revealed that gender and students interest playa significant influence on students’ choice of business education programme. Furthermore, thereis no significant difference between male and female students on their choice of option inbusiness education in universities. It was recommended, among others, that both male andfemale business education students should be encouraged to enrol into business educationprogrammes through the activities of their professional bodies and beneficiaries of theprogrammes.
Keywords: Business education, career choice, students’ interest, university